ALTERNATIF PEMBIAYAAN BARANG MODAL DENGAN LEASING - Istiarto Istiarto; I Made Sudana (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
Leasing is one of the ways used by companies to obtain funding at a cost which is relatively cheaper and easier. Financing by means of leasing has gained a lot of advantages that bring the company can maximize profits. Type leasing for lease to need capital goods used by the main feature of a capital lease/option rights for their special lease. The main characteristic of the lease capital lease types is the right option for lease to choose whether to give earlier capital goods at a cheaper price or do not buy at the end of the lease. Financing by means of leasing listed for lease financial position are reported as a fixed asset lease and lease obligation is the present value of the minimum lease payments in the future by showing a number of requirements, such as lease payments, interest rates, lease period and the estimated residual value